Thrombocytopenia and hyperprogression after radiotherapy and camrelizumab treatment in an esophageal cancer patient with increased JAK2 gene copies: a case report - Wang, Hang; Li, Yun; Qiu, Min; Wang, Jianmin (Frontiers in Oncology, 2024)
Radiotherapy (RT) and immune checkpoint inhibitor (ICI) are important treatments for esophageal cancer. Some studies have confirmed the safety and effectiveness of using RT in combination with ICI, while serious side effects have been exhibited by some patients. We report a patient with metastatic esophageal cancer who received RT combined with ICI. The patient experienced severe thrombocytopenia, and treatment with thrombopoietin and corticosteroids were ineffective. Finally, the patient developed abscopal hyperprogression outside the radiation field. Interestingly, next-generation sequencing revealed increased JAK2 gene copies in the surgical slices. The JAK2/STAT3 pathway is involved in the regulation of megakaryocyte development. Recurrent thrombocytopenia may activate the JAK2/STAT3 pathway, leading to megakaryocyte differentiation and platelet biogenesis. However, persistent activation of the JAK2/STAT3 pathway has been associated with immune ICI resistance and tumor progression. This case indicates that thrombocytopenia and increased JAK2 gene copies may be risk factors for poor prognosis after ICI and RT treatment.